KOMUNITAS TIONGHOA DALAM PUSARAN POLITIK: AKTIVITAS SOSIAL EKONOMI ETNIS TIONGHOA DI MOJOKERTO, 1959-1980 - Lukiyati Ningsih; Sarkawi B. Husain (Fakultas Ilmu Budaya universitas Hasanuddin, 2019)
This article discusses the social and economic activities of ethnic Chinese in Mojokerto between 1959 and 1980 and it shows that ethnic Chinese in Mojokerto conducted their economic activities close to the riverbanks of the Brantas River in Mojokerto area. Businesses owned by ethnic Chinese scattered over areas of Mojokerto. Ethnic Chinese in urban areas dominated trading activities at the city center located at Majapahit street while other activities, mainy agricultural activities, were spread in rural areas of the district. The implementation of the regulation PP 10 1959 forced Chinese population living in the countryside to move into the city. In East Java, the implementation of the regulation Pepelrada Jatim 1966 resulted in the changes of the attributes of Chineseness in economic activities in the area of Mojokerto. Keywords: Social Economic Activities, Mojokerto, Chinese